The right ventricular involvement in dilated cardiomyopathy: prevalence and prognostic implications of the often-neglected child - Manca, Paolo; Nuzzi, Vincenzo; Cannatà, Antonio; Castrichini, Matteo; Bromage, Daniel I.; De Luca, Antonio; Stolfo, Davide; Schulz, Uwe; Merlo, Marco; Sinagra, Gianfranco (Heart failure reviews, 2022)
Dilated cardiomyopathy (DCM) is a primary heart muscle disease characterized by left or biventricular systolic impairment. Historically, most of the clinical attention has been devoted to the evaluation of left ventricular function and morphology, while right ventricle (RV) has been for many years the forgotten chamber. Recently, progresses in cardiac imaging gave clinicians precious tools for the evaluation of RV, raising the awareness of the importance of biventricular assessment in DCM. Indeed, RV involvement is far from being uncommon in DCM, and the presence of right ventricular dysfunction (RVD) is one of the major negative prognostic determinants in DCM patients. However, some aspects such as the possible role of specific genetic mutations in determining the biventricular phenotype in DCM, or the lack of specific treatments able to primarily counteract RVD, still need research. In this review, we summarized the current knowledge on RV involvement in DCM, giving an overview on the epidemiology and pathogenetic mechanisms implicated in determining RVD. Furthermore, we discussed the imaging techniques to evaluate RV function and the role of RV failure in advanced heart failure.